2009
DOI: 10.1016/j.placenta.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin B Associates with Signal Transducer and Activator of Transcription 1 in Monocyte-Derived and Placental Macrophages

Abstract: Cystatin (CSTB, also known as stefin B), a cysteine protease inhibitor, recently was found to be down-regulated in the proteome of uninfected and HIV-1-infected placental macrophages (PM) and associated with restricted HIV-1 replication in PM but not in monocyte-derived macrophages (MDM). We investigated CSTB interactions with signal transducer and activator of transcription 1 (STAT-1) by immunoprecipitation studies because this molecule is known to activate HIV-1 replication. Since both CSTB and STAT-1 are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…They showed that stefin B interacted with several different proteins in HIV-1-infected macrophages, among others also two proteins involved in JAK/STAT signaling pathway [35]. Since stefin B influences the activation of STAT-1 [34] and STAT-3 (our results), we propose that it likely interferes with signaling pathway upstream of STAT-1 and STAT-3. The precise mechanism by which stefin B influences JAK/STAT signaling is yet to be determined.…”
Section: Discussionsupporting
confidence: 52%
“…They showed that stefin B interacted with several different proteins in HIV-1-infected macrophages, among others also two proteins involved in JAK/STAT signaling pathway [35]. Since stefin B influences the activation of STAT-1 [34] and STAT-3 (our results), we propose that it likely interferes with signaling pathway upstream of STAT-1 and STAT-3. The precise mechanism by which stefin B influences JAK/STAT signaling is yet to be determined.…”
Section: Discussionsupporting
confidence: 52%
“…A recent study found that cystatin B interacts with STAT-1, and tyrosine phosphorylation of this protein was higher in PM. This type of phosphorylation in STAT-1 is associated with decreased HIV transcription [20]. Further studies are needed to elucidate the signaling pathways for the observed restriction in PM.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of cathepsin B endogenous inhibitor; cystatin B show the importance of this protein in HIV-1 replication (Luciano-Montalvo and Meléndez 2009; Rivera-Rivera et al 2012) and in other conditions such as progressive myoclonus epilepsy (Lehtinen et al 2009). Our results show increased levels of secreted cystatin B from HIV-infected cocaine-treated MDM cultures compared to cocaine negative HIV infected cultures at 12dpi that parallels with the peak HIV replication.…”
Section: Discussionmentioning
confidence: 99%